Four distinct peer interaction variables as moderators of the fearful temperament‐anxiety association, using data from the Generation R Study - Anita Harrewijn; Rosa H. Mulder; Marinus H. vanIJzendoorn; Matthias J. Wieser; Pauline W. Jansen (JCPP Advances)
Abstract Background Pediatric anxiety disorders are common and have severe long‐term consequences. Early‐life fearful temperament is a predictor of later anxiety, but not all children with highly fearful temperament will eventually develop an anxiety disorder. Therefore, it is important to identify factors that moderate the fearful temperament‐anxiety association. The goal of this study it to replicate the fearful temperament‐anxiety association in a large cohort study, explore sex as a moderator of this association, and to investigate four distinct peer interaction variables as moderators of this association. Methods 2730 children (51.0% girls) with parent‐reported fearful temperament at 6 months and parent‐reported anxiety symptoms at 13 years were included from a prospective cohort study (Generation R Study). Fearful temperament was also observed in a subset (n = 643, 49.3% girls) of these children. Peer interactions were measured in four different ways: mother‐reported victimization (at age 7), self‐reported friendship quality (at age 9), and self‐reported feelings and facial expressions during social exclusion in a lab‐based task (at age 9). Results Children with higher parent‐reported, but not observed, fearful temperament showed more anxiety symptoms as adolescents, β = 0.07, p < 0.001. This association was not moderated by sex, β = −0.07, p = 0.07, but was stronger in adolescents who reported more negative feelings after social exclusion, β = 0.05, p = 0.04. Victimization, friendship quality, and sad facial expressions were related to increased anxiety symptoms but did not moderate the fearful temperament‐anxiety association. Conclusions We showed that parent‐reported fearful temperament and anxiety were associated in this large community sample and that this association was not moderated by sex. Additionally, we showed that negative feelings after social exclusion moderated this association. Potentially, children with a highly fearful temperament might benefit from learning how to cope with social exclusion. Future studies are needed to confirm our findings and could focus on the potential role of coping with social rejection in interventions.